Seminar Sex Education dan Bahaya NAPZA untuk Mereduksi Kenakalan Remaja Desa Sumbersari Megaluh Jombang - Septian Ragil Anandita; Muh. Khofif Luthfi Rohman; Andi Franoto; Siti Aminatuz Zuhria; Mohammad Ja'far Sodiq Maksum; Faisol Hidayatulloh (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this community service activity is to increase youth knowledge about sex education and drugs and to innovate in handling and eradicating drug abuse in the Sumbersari village environment. Sumbersari village itself is quite minimal in knowledge about sex education and drugs in adolescents. Even though Sumbersari village is a village that has a thick religious culture. However, they consider sex education and drugs to be negative things. Research is an activity process of seeking and finding answers that are used to solve a problem. Judging from the data obtained and making direct observations. The research method used is Community Based Research (CBR). Implementation of community service activities in the Community Partnership Program (PKM) scheme. The implementation of the program carried out in this service is an extension and assistance program for the community, especially among adolescents in preventing drug abuse and the importance of sex education. This program is a form of implementation in the form of dedication. This program is also implemented as a program that is needed by the Sumbersari village community. Community service activities have been successfully carried out and running smoothly. The success of the activity can be seen from the enthusiasm of the participants and the evaluation results of the activities which are considered good or even very good for several aspects. Hopefully, this seminar on sex education and drugs will increase the reduction of juvenile delinquency from other aspects, such as smoking habits in early childhood, rampant promiscuity in adolescents, and adolescent dependence on certain drugs.